2024
DOI: 10.1109/tem.2021.3117884
|View full text |Cite
|
Sign up to set email alerts
|

Why Do People Use Artificial Intelligence (AI)-Enabled Voice Assistants?

Abstract: Artificial Intelligence (AI)-enabled voice-assistants such as Alexa and Siri are increasingly replacing the search engines since the consumers are actively using them for accomplishing a variety of their day-to-day tasks.Technology providers as well as marketers increasingly focus on leveraging the use of voice assistants to engage their customers and offer them more personalized value propositions. The study examines the different consumption values associated with the use of voice-assistants. Based on a theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 79 publications
0
22
0
Order By: Relevance
“…Consumers’ rapid adoption and daily use of artificial intelligence (AI)-enabled voice assistants (VAs), such as “Alexa”, “Bixby”, “OK Google” and “Siri”, has redefined the dimensions of service delivery by offering consumers unparalleled autonomy and immediacy (Chouk and Mani, 2019; Fernandes and Oliveira, 2021; Klaus and Zaichkowsky, 2020; Lucia-Palacios and Pérez-López, 2021; Mogaji and Nguyen, 2021). Consumers now conduct routine activities, such as information search and controlling the climate of their surrounding environment, with the support of VAs (Malodia et al , 2021; McLean et al , 2021). Facilitating this trend, firms are integrating VAs into their products and services to offer highly personalised and efficient services to their customers (Fernandes and Oliveira, 2021; Klaus and Zaichkowsky, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumers’ rapid adoption and daily use of artificial intelligence (AI)-enabled voice assistants (VAs), such as “Alexa”, “Bixby”, “OK Google” and “Siri”, has redefined the dimensions of service delivery by offering consumers unparalleled autonomy and immediacy (Chouk and Mani, 2019; Fernandes and Oliveira, 2021; Klaus and Zaichkowsky, 2020; Lucia-Palacios and Pérez-López, 2021; Mogaji and Nguyen, 2021). Consumers now conduct routine activities, such as information search and controlling the climate of their surrounding environment, with the support of VAs (Malodia et al , 2021; McLean et al , 2021). Facilitating this trend, firms are integrating VAs into their products and services to offer highly personalised and efficient services to their customers (Fernandes and Oliveira, 2021; Klaus and Zaichkowsky, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Facilitating this trend, firms are integrating VAs into their products and services to offer highly personalised and efficient services to their customers (Fernandes and Oliveira, 2021; Klaus and Zaichkowsky, 2020). For example, VA integration is becoming a common feature in automobiles, electronics and home appliances (Malodia et al , 2021). Thus, VAs, which are rapidly embedding themselves in consumers' day-to-day lives, are set to revolutionise the way marketers engage with customers (McLean et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We hear more synthesized voices in our daily lives than ever before. Voice assistants, such as Apple's Siri, Amazon's Alexa, Microsoft's Cortana, and Google's Assistant, use synthesized human speech to communicate with us in our homes [1], [2]. Virtual assistants answer customer service phone numbers and create synthetic voices as they assist us.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence (AI)-based apps increase functionality, and practitioners have found that retail performance is subsequently improved that leverage reinforces customer experience (Malodia et al, 2021). Businesses' widespread application of AI is seen as necessary for determining the direction of doing business in the emerging technology era (Awan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence (AI)-based apps increase functionality, and practitioners have found that retail performance is subsequently improved that leverage reinforces customer experience (Malodia et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%